Underdiagnosis of Chronic Obstructive Pulmonary Disease: A Rationale for Spirometry as a Screening Tool - R Andrew McIvor; Donald P Tashkin (Canadian Respiratory Journal)
Chronic obstructive pulmonary disease (COPD) is associated with significant morbidity and mortality. It is the fourth leading cause of death in the United States, and its impact on quality of life can be severe. The debate on spirometry as a screening tool has been raised and dropped on various occasions over the past 30 years. This paper readdresses the debate in the light of recent evidence from population studies. Spirometry is an underused, easy to perform office-based procedure that has been further facilitated by the advent of modern technology. Despite the fact that spirometry is the gold standard for the diagnosis and assessment of COPD, mass screening using this tool remains controversial. This article provides a discussion based on a recent review of the literature regarding the current and future status of spirometry as a screening tool. A thoughtful approach to spirometry screening should include assessments of the magnitude of underdiagnosis, potential effectiveness of intervention, predictive value of spirometry and clinical profile of patients with COPD.